The development of a novel type of microelectrodes to evaluate the reactivity of fine sulphide mineral particles. (15th June 2022) - Chen, Xumeng; Shi, Zhiming; Peng, Yongjun
Highlights: Single-layer particle microelectrodes were developed for measuring the reactivity of fine particles. This new type of microelectrodes preserved all electrochemical characteristics of minerals. Pyrite reactivity increased with a decrease in particle size. Pyrite reactivity increased exponentially when particle size decreased to around 20 µm. The design of regrinding was recommended to consider the critical size for electrochemical reactivity. Abstract: Electrochemical reactivity of sulphide minerals has a strong effect on pulp chemistry and hence mineral flotation behaviours. A great number of flotation plants is experiencing difficulties in separating sulphide minerals at cleaner flotation after the rougher flotation concentrates are reground to small particle sizes. Bulk electrodes prepared from large mineral crystals have been used to investigate the reactivity of sulphide minerals, but they cannot represent the minerals at micro sizes in practice. In this study, a novel type of single-layer particle microelectrodes was developed for measuring the reactivity of fine particles. This type of microelectrodes used a conductive double side carbon tape as the substrate which had a minimum interference with the electrochemical signals of minerals. These microelectrodes were then used to evaluate the reactivity of pyrite particles of different sizes by measuring the corrosion current density from polarisation curves. It was interesting to find that pyrite reactivity increased with a decrease in particle size and there was an exponential increase in reactivity when particle size decreased to around 20 µm. This study recommends the critical size, beyond which electrochemical reactivity increases dramatically, to be considered when the regrinding process is designed together with the particle size for mineral liberation.